Physiotherapy and Anterior Resection Syndrome (PARiS) trial: feasibility study protocol. Issue 6 (30th June 2018) - Powell-Chandler, Anna; Rees, Buddug; Broad, Carole; Torkington, Jared; O'Neill, Claire; Cornish, Julie A
Abstract : Introduction: Rectal cancer affects more than 600 patients per year in Wales, with a 5-year survival rate of around 60%. A recent report demonstrated that 19% of patients with bowel cancer had difficulty controlling their bowels after surgery, and these patients were twice as likely to report lower quality of life than those who had control. Nearly all patients will experience bowel dysfunction initially following surgery and up to 25% will experience severe bowel dysfunction on a long-term basis. The aim of this study is to test the feasibility of introducing a simple intervention in an attempt to improve bowel function following surgery for rectal cancer. We propose the introduction of an educational session from specialist nurses and physiotherapists prior to surgery and a subsequent physiotherapy programme for 3 months to teach patients how to strengthen their pelvic floor. Methods and analysis: All patients with rectal cancer planned to receive an anterior resection will be approached for the study. The study will take place in three centres over 12 months, and we expect to recruit 40 patients. The primary outcome measure is the proportion of eligible patients approached who consent to and attend the educational session. The secondary outcomes include patient compliance to the pelvic floor rehabilitation programme (assessed by patient paper or electronic diary), the acceptability of the intervention to the patient (assessed using qualitative interviews) and preoperative and postoperative pelvic floor tone (assessed using the Oxford Grading System and the International Continence Society Grading System), patient bowel function and patient quality of life (assessed using validated questionnaires). Ethics and dissemination: Ethics approval was granted. This feasibility study is in progress. If patients find the intervention acceptable, the next stage would be a trial comparing outcomes after anterior resection in those who have and do not have physiotherapy. Trial registration number: ISRCTN77383505 ; Pre-results.